2015
DOI: 10.1002/acr.22608
|View full text |Cite
|
Sign up to set email alerts
|

Greater Lateral Femorotibial Cartilage Loss in Osteoarthritis Initiative Participants With Incident Total Knee Arthroplasty: A Prospective Cohort Study

Abstract: Purpose To explore whether baseline to 12-month follow-up (M) change in femorotibial cartilage thickness (differs between subjects who received a KR between 24M and 60M from those without KR. Methods In this prospective cohort study, 531 right knees from Osteoarthritis Initiative participants with definite radiographic KOA (KLG2–4) were studied. Segmentation was applied to coronal fast low angle shot (FLASH) magnetic resonance images (MRI), to quantitatively determine cartilage thickness in 16 femorotibial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“… 45 The study design and the fact that the imaging data were restricted to X-rays may have been important limiting factors of this report. The observation of the association of TKA with the progression of valgus malalignment and cartilage loss in the global knee and lateral compartment in women extends the existing knowledge from previous studies 36 , 37 and could be an explanation for the association between BML and TKA being found only in women.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“… 45 The study design and the fact that the imaging data were restricted to X-rays may have been important limiting factors of this report. The observation of the association of TKA with the progression of valgus malalignment and cartilage loss in the global knee and lateral compartment in women extends the existing knowledge from previous studies 36 , 37 and could be an explanation for the association between BML and TKA being found only in women.…”
Section: Discussionsupporting
confidence: 83%
“…As malalignment is a well-known factor associated with cartilage loss, it could provide a possible explanation for the higher incidence of TKA. 7 , 16 , 17 , 36 , 37 …”
Section: Discussionmentioning
confidence: 99%
“…A previous report from 2003 by Escobar et al tried to identify factors for the appropriateness of the indication for TKR in patients with osteoarthritis by using a modified Delphi panel judgment based on outcome measures and confirmed that symptomatology and radiology explained most of the variability in the appropriateness of indication [14]. A previous study by Hitzl et al [15] revealed that individuals receiving a TKR within a period of 4 years displayed a significantly reduced cartilage thickness at base-line when compared to controls, indicating a change in structure; here, the magnetic resonance imaging (MRI) parameter is a predicting factor that can guide a surgeon's decision for performing TKR surgery.…”
Section: Introductionmentioning
confidence: 94%
“…Notably, the results of one study showed that patients who had been treated with intra-articular glucocorticoids (40 mg triamcinolone) had significantly greater cartilage volume loss than those who had been given intra-articular saline over a 2 year period (between group difference −0.11mm; 95% CI −0.20 to −0.03mm) 55 . This result is concerning because a 1% increase in the rate of tibial cartilage loss between baseline and 2 years corresponds to an ~20% increase in the risk of undergoing knee replacement surgery at 4 years 56 and because high rates of cartilage loss have been directly associated with an increased risk of undergoing arthroplasty 57 .…”
Section: Standard Intra-articular Treatmentsmentioning
confidence: 99%